Fabrication of Fe-2.1 wt.% Si Alloy Sheets with Dominant Goss Texture Through Thickness - Shan,Ning (2019)
Macro- and micro-texture of Fe-2.1 wt.% Si alloy sheets were investigated and analyzed by X-ray diffraction and electron backscattered diffraction techniques. A Goss ({110}<001>) component accompanied by extremely weak γ (<111>//ND, normal direction) fiber is successfully formed through the sheet thickness after primary recrystallization and considerable grain growth. Goss grains mainly nucleate at shear bands in various deformed matrices with orientations spreading from <112>//ND to <332>//ND fibers. The formation of dominant Goss recrystallization texture through the thickness can be attributed to the suppression of the nucleation at grain boundaries of γ deformed matrices and the promotion of the nucleation at shear bands in various deformed matrices, based on optimization of the initial texture and microstructure and the applied processing parameters.